Direct Production of Reactive Oxygen Species from Aggregating Proteins and Peptides Implicated in the Pathogenesis of Neurodegenerative Diseases - Tabner, Brian J.; Turnbull, Stuart; El-Agnaf, Omar M.A.; Allsop, David (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2003)
The deposition of abnormal protein fibrils is a prominent pathological feature of many different 'protein conformational' diseases, including some important neurodegenerative diseases. Some of the fibril-forming proteins or peptides associated with these diseases have been shown to be toxic to cells in culture. A clear understanding of the molecular mechanisms responsible for this toxicity should shed light on the probable link between protein deposition and cell loss in these diseases. In the case of the β-amyloid (Aβ) peptide, which accumulates in the brain in Alzheimer's disease, there is good evidence that the toxic mechanism involves the production of reactive oxygen species (ROS). By means of an electron spin resonance (ESR) spin-trapping method, we have shown that solutions of Aβ liberate hydroxyl radicals when incubated in vitro, upon the addition of small amounts of Fe(II). We have also obtained similar results with α-synuclein, which accumulates in Lewy bodies in Parkinson's disease, and with the PrP (106-126) toxic fragment of the prion protein. It is becoming clear that some transition metal ions, especially Fe(III) and Cu(II), can bind to these aggregating peptides, and that some of them can reduce the oxidation state of Fe(III) and / or Cu(II). The data suggest that hydrogen peroxide accumulates during incubation of these various proteins and peptides, and is subsequently converted to hydroxyl radicals in the presence of redox-active transition metal ions. Consequently, a fundamental molecular mechanism underlying the pathogenesis of cell death in several different neurodegenerative diseases could be the direct production of ROS during formation of the abnormal protein aggregates.
Keywords: protein